2019
DOI: 10.1016/j.trf.2019.07.012
|View full text |Cite
|
Sign up to set email alerts
|

Driving attitudes, behaviours, risk perception and risk concern among young student car-drivers, motorcyclists and pedestrians in various EU countries

Abstract: a b s t r a c tThe number of car crashes has gradually reduced in the last decade across all European Countries, but the number of motorcycle crashes has remained nearly the same. In our research we investigate whether there are differences in attitudes towards road safety issues, driving behaviours in specific imagined situations, risk perception and risk concern, among young student drivers and riders. The study involved a large sample taken from across six European countries.The results reveal that although… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 38 publications
1
12
0
Order By: Relevance
“…Therefore, we considered risk perception: several studies have shown how road risk perception influences engagement in risky behaviors (Cordellieri et al, 2019;Piccardi et al, 2021), indeed, our results appear to support the hypothesis that the variable perception of risk in driving mobile phone use, influences the variable multitasking.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Therefore, we considered risk perception: several studies have shown how road risk perception influences engagement in risky behaviors (Cordellieri et al, 2019;Piccardi et al, 2021), indeed, our results appear to support the hypothesis that the variable perception of risk in driving mobile phone use, influences the variable multitasking.…”
Section: Discussionsupporting
confidence: 76%
“…In particular, Glendon et al (1996) showed that young male drivers tend to underestimate their personal perception of risk and overestimate their competence compared to women. Recent studies have addressed gender differences in different risk profiles, demonstrating a higher risk tendency among adolescent males, although the level of risk perception was found to be the same in both genders (Cordellieri et al, 2016(Cordellieri et al, , 2019.…”
Section: Risk Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…They have greater chance to ignore the consideration of risk perceptions in the decision-making process. A recent study by Cordellieri et al [6] mentioned that the most vulnerable group regarding deaths due to road crashes is the young-age group, namely, aged between 15 and 29. They stated that the young-age group is normally related to a higher risk of being involved in a road crash, for instance, speeding, drunk riding, and a lack of observation and signaling at intersections.…”
Section: Discussionmentioning
confidence: 99%
“…Although the level of risk perception during driving behavior is the same for both motorcyclists and car drivers, the level of concern of motorcyclists about the risk of road accidents is less than that of car drivers. This leads to a higher possibility of risky driving behavior in motorcyclists than that in car drivers [6].…”
Section: Introductionmentioning
confidence: 99%